Experimental Study on the Influence of Particle Diameter, Mass Concentration, and Impeller Material on the Wear Performance of Solid–Liquid Two-Phase Centrifugal Pump Blade - Wang, Yanping; Li, Weiqin; He, Tielin; Liu, Hao; Han, Chuanfeng; Zhu, Zucao (Frontiers in Energy Research, 2022)
The effect of three factors including the diameter of solid particles, the mass concentration of particles and the material of impellers on the wear of solid-liquid two-phase centrifugal pump was studied by wear experiment. The solid particles are SiO2 with irregularly shaped, and the diameter ranges are 0.125mm-0.212mm, 0.212mm-0.425mm, and 0.425mm-0.710mm. The mass concentration of solid particles is 15%, 20% 30% respectively. The material of impellers are carbon structural steel (Q235), grey cast iron (HT200) and low alloy high strength steel (16Mn), respectively. The amount of wear is determined by measuring the thickness of impeller material before and after wear experiments. The wear morphology of the impeller was observed by using a digital microscope. The possible erosion wear mechanism was discussed. Moreover, the wear of impeller was numerically simulated under different mass concentrations and different particle diameters. Comparing the serious wear positions of the impeller, the experimental results are correspond well with the numerical simulation